time-calibrated phylogenetic approach to assessing the phylogeography, colonization history and phenotypic evolution of snakes in the Japanese Izu Islands - Kuriyama, Takeo; Brandley, Matthew C.; Katayama, Akira; Mori, Akira; Honda, Masanao; Hasegawa, Masami (Journal of biogeography, 2011)
Aim We infer the biogeography and colonization history of a dispersal-limited terrestrial vertebrate, the Japanese four-lined ratsnake (Elaphe quadrivirgata), to reveal the number of times mainland populations have invaded the Izu Archipelago of Japan, the mainland sources of these colonists, and the time-scale of colonization. We compare these results with those of past studies in an attempt to uncover general biogeographical patterns. Moreover, we briefly examine the significance of colonization history when evaluating the evolution of body size and melanism of the Izu Island E. quadrivirgata populations. Location The Izu Islands (Oshima, Toshima, Niijima, Shikine, Kozu, Tadanae and Mikura), a volcanic archipelago off the Pacific coast of central Japan. Methods We obtained DNA sequences of the mitochondrial cytochrome b gene (1117 base pairs) from 373 individual snakes sampled from seven of the Izu Islands and 25 mainland localities. We employed partitioned Bayesian phylogenetic analyses assuming a relaxed molecular clock to estimate phylogenetic relationships among extant haplotypes and to give an explicit temporal scale to the timing of clade divergence, colonization history and tempo of body-size evolution. Moreover, we employed model-based biogeographical analysis to calculate the minimum number of times E. quadrivirgata colonized the Izu Islands. Results We found evidence that three separate regions of the Izu Archipelago have been colonized independently from mainland ancestors within the past 0.58-0.20 Ma. The Izu Peninsula plus Oshima and Mikura were both colonized independently from lineages inhabiting eastern mainland Japan. The Toshima, Niijima, Shikine, Kozu and Tadanae populations all derive from a single colonization from western mainland Japan. Oshima has been subject to three or possibly four colonizations. Main conclusions These results support the hypothesis that the extreme body-size disparity among island populations of this ratsnake evolved in situ. Moreover, the fact that the dwarf, melanistic population inhabiting Oshima descends from multiple mainland colonization events is evidence of an extremely strong natural selection pressure resulting in the rapid evolution of this unique morphology. These results contrast with theoretical predictions that natural selection pressures should play a decreased role on islands close to the mainland and/or subject to frequent or recent immigration.